THE PERFORMANCE OF CONSTRUCTION HEALTH AND SAFETY OFFICERS - John SMALLWOOD; Claire DEACON (Journal of Construction Project Management and Innovation)
Full-time or part-time construction health and safety officers (CHSOs) are a requirement in terms of the South African Construction Regulations. Previous research findings and anecdotal evidence indicate that CHSOs are lacking in various competencies, are excluded from contributing to the management of health and safety (H&S) and sites, could be more effective, and require development. The objectives of the study were to determine the performance of CHSOs, barriers to the contribution of CHSOs to construction and construction H&S, and the potential of interventions to contribute to an improvement in CHSOs’ contribution to and impact on construction and construction H&S. A descriptive survey method was adopted for gathering and processing data obtained through self-administered questionnaires. The sample stratum included a convenience sample of delegates attending a two-day construction H&S summit. The findings indicate that the contribution of CHSOs to H&S could be improved. Various factors constitute a barrier to CHSOs contributing to H&S. These include exclusion from decision-making, non-consultation by site management, lack of authority, and exclusion from managing sites, which constitutes marginalisation. This is underscored by the low ratings of CHSOs in their understanding and appreciation of various aspects, composite knowledge areas and skills, and the extent to which interventions could contribute to an improvement in the contribution of CHSOs to H&S and construction. Conclusions include that the function of CHSOs is important, and that the “CHSO” requirement in terms of the Construction Regulations is justified, that inadequate ‘construction’ knowledge and experience contributes to the exclusion of CHSOs from managing sites, and the actual barrier of CHSOs contributing to H&S, and that formal qualifications would empower CHSOs to contribute optimally to H&S and construction.